Canibalismo e normalização - Carvalho, Eliane Knorr de (2008)
Cannibalism is a Western invention. It is applied to indigenous groups and is expressed in different ways according to each society, place, time and context. Among Amerindians in the 16th and 17th centuries, these practices could be identified in warrior and death rites. However, anthropophagy among the indigenous people was also used by the European colonizers as a justification for applying preventive and punitive measures and technologies of subjection. In Western societies, cannibalism is understood in different contexts. Extreme situations, in which cannibalism is the last resource for survival, are currently the only acceptable circumstances for the practice. Cannibalism as a tactic of terror gathers all these other circumstances. Instead of the facts, the effects of cannibalism in the discourse are at stake. The third case analyzed in this dissertation is cannibalism as a crime without a reason, which serves as justification for the psychiatric knowledge and justifies its application. Along with new power technologies of the society of control, and among the so-called crimes without a reason, another possibility of cannibalism in Western society emerges: a cannibalism in which the victim is volunteer. The research seeks to identify the existence of cannibalism through an analysis of discourse, based on Michel Foucault s propositions. It uses as analytical tool the notions and concepts of a few authors, namely Claude Lévi-Strauss, Michel Foucault e Gilles Deleuze